Sedemdeset let jezikovne zgodovinarke Majde Merše - Legan Ravnikar, Andreja (Slavia Centralis, 2020)
The article presents the scientific research work of linguist dr. Majda Merše, who celebrated her 70th birthday in August 2019.
Keywords: Majda Merše; linguist; scientific research work; history of language; historical linguistics